2000
DOI: 10.1002/(sici)1520-6378(200006)25:3<226::aid-col11>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Threshold color differences compared to supra-threshold color differences

Abstract: Threshold color difference ellipses, as represented by the MacAdam ellipses have been compared to unit contours implicit in the CIE94 color difference formula, found to represent small supra‐threshold color differences well, both in the CIE chromaticity diagram as well as the a*, b* diagram. The results indicate that the two types of contours are significantly different. While threshold differences are well described by incremental changes in cone sensitivity supra‐threshold differences are well‐described by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is recognized that as the magnitude of color difference increases from threshold to suprathreshold, the contours that describe equally perceived color difference change shape. [31][32][33][34] However, there is not enough data in this experiment to draw any firm conclusions about the differences in sensitivity to color difference based on the location of the color. A multiple comparison of 2-way ANOVA analysis between adjustment methods and observer expertise was performed ( Fig.…”
Section: Matching Experimentsmentioning
confidence: 84%
“…It is recognized that as the magnitude of color difference increases from threshold to suprathreshold, the contours that describe equally perceived color difference change shape. [31][32][33][34] However, there is not enough data in this experiment to draw any firm conclusions about the differences in sensitivity to color difference based on the location of the color. A multiple comparison of 2-way ANOVA analysis between adjustment methods and observer expertise was performed ( Fig.…”
Section: Matching Experimentsmentioning
confidence: 84%
“…Figure 3(C) shows that the reddish-yellow (hue angle of 45°) was the hardest color to make a match, while the greenish-blue (hue angle of 195°) was the easiest with significantly better performance than the reddish-yellow and the yellowish-green (hue angle of 125°). [31][32][33][34] However, there is not enough data in this experiment to draw any firm conclusions about the differences in sensitivity to color difference based on the location of the color. There is a trend [see Fig.…”
Section: Matching Experimentsmentioning
confidence: 84%
“…Thus, the last CIE recommendation for industrial colordifference evaluation 22 has been suggested for moderate color differences between 0 -5 CIELAB units and changes between threshold and suprathreshold color difference perception have also been reported. 23 On this basis, it might also be asked whether the distinction of the color attributes varies with the magnitude of the color difference, and this was considered in the design of our two experiments, as explained before. In our case, given that we based our experiments on samples from the Munsell atlas, 5 the color differences of the pairs in all cases were far greater than thresholds, as indicated by the second column of Tables I and II.…”
Section: Magnitude Of Color Differencesmentioning
confidence: 99%